Konflik Peran Ganda, Coping Stress Dan Dukungan Sosial Sebagai Prediktor Kesejahteraan Hidup Pada Perawat - Widyasrini, Jati Uji Sekti, Dr. Sri Lestari, M.Si (2016)
The research aims to test empirically multiple roles conflict, stress coping and social support as predictors of subjective well-being to the nurses. The hypothesis being tested is the relationship between multiple roles conflict, stress coping and social support toward subjective well-being. This type of research is a correlation quantitative research with data collection technique using 4 scales, there are subjective well-being scale, multiple roles conflict scale, stress coping scale and social support scale. The sampling technique used a random cluster sampling. The location of research is at the Semarang Hospital with nurses as respondents who numbered 123 people. Based on data analysis by using multiple regression analysis got a result that there was a significant relationship between multiple roles conflict, stress coping and social support toward subjective well-being. Effective contribution of multiple roles conflict, stress coping and social support toward subjective well-being is 27,5%. From the three predictors of subjective well-being, social support is a highest predictor. Variable aspect of multiple roles conflict has a negative effect on subjective well-being. It means that the higher multiple roles conflict experienced by nurses can reduce the subjective well-being of nurses. While variable aspect of social support has a greater positive effect than the variable aspect of coping stress for the subjective well-being of nurses. It means that the higher social support performed by nurses and the greater coping stress received by nurses then the subjective well-being of nurses will get higher. An implication for psychology is as an evaluation and takes the role of psychology in an effort to improve the subjective well-being for nurses.